2017
DOI: 10.1186/s40497-017-0079-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing mission statements of social enterprises and corporate enterprises in the new and renewable energy sector of India: a computer aided content analysis study

Abstract: This paper aims to explore how differently corporate enterprises and social enterprises strategically position themselves through their mission statements. The most notable distinctions between the mission statements of both groups exist in the degree of action orientation, endorsements of people/groups, and the highlights of positive entailment. The new and renewable energy sector is playing a key role in the emergence of India as an environmentally conscious emerging economy. The enterprises instrumental in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The structure is particularly important in creating new renewable energy markets for the rural population and the base of the pyramid (BOP). Reference [30] applies a comparative model of social enterprise and enterprise in the field of new and renewable energies and find that the most notable differences between the models of both groups are in the degree of action orientation and approval of people/groups and the high points of positive engagement in the field of renewable energies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The structure is particularly important in creating new renewable energy markets for the rural population and the base of the pyramid (BOP). Reference [30] applies a comparative model of social enterprise and enterprise in the field of new and renewable energies and find that the most notable differences between the models of both groups are in the degree of action orientation and approval of people/groups and the high points of positive engagement in the field of renewable energies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Increasingly, private sector companies have been invited into the new and renewable energy (NRE) sector to help provide public services where governments cannot reach (Martinot et al, 2002;Surana and Anadon, 2015). These companies often take the form of social enterprises, focus on addressing social and environmental challenges at a societal level through innovative business models (Mair and Marti, 2009;Doherty et al, 2014;Haugh and Talwar, 2016;Sengupta and Sahay, 2017b). In the NRE sector, social enterprises predominently focus on small scale renewables or expanding electricity access through decentralised systems (Jolly et al, 2012;Sonne, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge has great importance not only in hightech sectors but also in agriculture that witnesses great dynamics of innovation, development of digitisation, transfer of knowledge into practice., In terms of competitiveness and achieving competitive advantage, knowledge is a prerequisite for its long-term achievement being confirmed by results from focus group and the other surveys in other countries (Cuervo-Cazurra and Rui 2017;Cozzolino and Rothaermel 2018;Saranga et al 2019;Stacho et al 2020). The results based on a literature review (Džupina 2017;Sengupta and Sahay 2017) showed that it is necessary to set the vision, mission of the organisation, and the organisation-wide strategy in each organisation, including the strategy of human resources management. A similar survey in the area of strategic management was applied in the Slovak Republic and Poland (Stacho et al 2015;Stasiak-Betlejewska 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The mission and the vision are at the top of the pyramid. Their goal is to mobilise and motivate employees to achieve the organisation's goals (Džupina 2017;Sengupta and Sahay 2017) and its basic direction (Aguilar- Barrientos et al 2015). Mission and the vision are followed by other strategic documents that are specific and focused on individual areas of the organization (David et al 2014;Zakayo 2018).…”
mentioning
confidence: 99%